Characterization of whole genome amplified (WGA) DNA for use in genotyping assay development - Han, Tao; Chang, Ching-Wei; Kwekel, Joshua C; Chen, Ying; Ge, Yun; Martinez-Murillo, Francisco; Roscoe, Donna; Težak, Živana; Philip, Reena; Bijwaard, Karen; Fuscoe, James C (BMC genomics, 2012)
Background Genotyping assays often require substantial amounts of DNA. To overcome the problem of limiting amounts of available DNA, Whole Genome Amplification (WGA) methods have been developed. The multiple displacement amplification (MDA) method using Φ29 polymerase has become the preferred choice due to its high processivity and low error rate. However, the uniformity and fidelity of the amplification process across the genome has not been extensively characterized. Results To assess amplification uniformity, we used array-based comparative genomic hybridization (aCGH) to evaluate DNA copy number variations (CNVs) in DNAs amplified by two MDA kits: GenomiPhi and REPLI-g. The Agilent Human CGH array containing nearly one million probes was used in this study together with DNAs from a normal subject and 2 cystic fibrosis (CF) patients. Each DNA sample was amplified 4 independent times and compared to its native unamplified DNA. Komogorov distances and Phi correlations showed a high consistency within each sample group. Less than 2% of the probes showed more than 2-fold CNV introduced by the amplification process. The two amplification kits, REPLI-g and GenomiPhi, generate very similar amplified DNA samples despite the differences between the unamplified and amplified DNA samples. The results from aCGH analysis indicated that there were no obvious CNVs in the CFTR gene region due to WGA when compared to unamplified DNA. This was confirmed by quantitative real-time PCR copy number assays at 10 locations within the CFTR gene. DNA sequencing analysis of a 2-kb region within the CFTR gene showed no mutations introduced by WGA. Conclusion The relatively high uniformity and consistency of the WGA process, coupled with the low replication error rate, suggests that WGA DNA may be suitable for accurate genotyping. Regions of the genome that were consistently under-amplified were found to contain higher than average GC content. Because of the consistent differences between the WGA DNA and the native unamplified DNA, characterization of the genomic region of interest, as described here, will be necessary to ensure the reliability of genotyping results from WGA DNA.